2006
DOI: 10.1017/s0022029905001573
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of simplified sampling procedures for estimating milk composition in dairy ewes

Abstract: Simplified designs of milk-composition recording, based on information from a single monthly milking, adjusted or not for interval between milkings and for milk yield, were simulated and evaluated for 2553 ewe-test-day records belonging to 155 lactations of Churra dairy ewes. Accuracy of simplified methods was evaluated by comparing estimated trait values (fat, protein, casein and total solid yields) with those observed both in a reference plan, where the two daily milkings were recorded at weekly intervals (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
1
6
0
1
Order By: Relevance
“…Research on this topic has examined various milk recording plans based on recording only one milking a day, their evaluation being usually carried out on the basis of twice-a-day monthly measures and under an intensive production system (three lambing times in 2 years). There are few reported studies using more informative data sets (with reduced recording intervals), as a more accurate comparative basis for milk yield (Gonzalo et al 2003) or milk composition (Othmane et al 2006a). Both studies reported high errors when comparing yields from simplified monthly plans with yield based on records collected weekly (A1).…”
mentioning
confidence: 99%
“…Research on this topic has examined various milk recording plans based on recording only one milking a day, their evaluation being usually carried out on the basis of twice-a-day monthly measures and under an intensive production system (three lambing times in 2 years). There are few reported studies using more informative data sets (with reduced recording intervals), as a more accurate comparative basis for milk yield (Gonzalo et al 2003) or milk composition (Othmane et al 2006a). Both studies reported high errors when comparing yields from simplified monthly plans with yield based on records collected weekly (A1).…”
mentioning
confidence: 99%
“…The alternate methods had been reported to be the most efficient simplified milk recording designs to estimate milk yield and composition (Gabiña et al, 1986;Gonzalo et al, 2003;Othmane et al, 2006;Othmane and Trabelsi, 2007;Othmane et al, 2011); but there was no available information on the impact of their adoption on genetic parameters and animal genetic evaluation allowing them to be judged as milk recoding designs for genetic improvement programs. In our study, the genetic variance component estimation showed that the adjusted alternate methods seemed more accurate; they had the lowest residual variances which were the closest to that observed with the reference method in both monthly and bimonthly milk recording designs.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation after implementation of new factors for the alternate plan in use indicated that the adoption of the pair of factors (1.7, 2.3) may remove by more than 13% the lack of fit associated to old factors (Othmane and Trabelsi, 2007). On the other hand, accuracy of these alternate methods, as simplified milk recording designs, is usually evaluated using lactation data sets where variation in a.m.-p.m. milk production would be compensated from one test-day to another, provided the number of test-days is sufficient (Othmane et al, 2006). This is not the case with test-day data sets that override the use of lactation data sets in many genetic improvement programmes in ewes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pour alléger les charges, de nombreux travaux de recherche ont envisagé de simpli fier les protocoles de contrôle laitier (1,6,8,11) et de croissance (2, 13) des ovins. En Tunisie, le contrôle de croissance des ovins allaitants nécessite au moins cinq à six visites d'un technicien à 21 jours d'intervalle, ce qui est très onéreux.…”
Section: Résuméunclassified